Peran dan Fungsi Tauhid Dalam Kehidupan Sosial - Devia Maharani Lubis; Reza Noprial Lubis; Siska Wulan Dari Lubis (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Tawhid has various functions and roles that can have a positive impact on social life, namely freeing humans from spreading mentality and worship to all creatures, protecting humans from false values ​​​​that are based on lust, power madness, and mere sensual pleasures. As a framework for thinking in the development of science and technology, as a foundation of faith that also guarantees the happiness and well-being of all mankind, when all its teachings are implemented consistently, teaching Muslims to make Allah SWT the center of their intellectual awareness. So it is clear that tauhid is closely related to social life because with tauhid humans can know the purpose of their lives, namely worshiping Allah Subhanahu Wata'ala vertically, namely directly to Allah with makdoh worship and horizontally, namely worshiping with fellow creatures of Allah with ghoirumakdoh worship.